Rendang Quality Assessment Freshwater mussels (Pilsbryoconcha exilis) With Different Size Weight - Nova Jumaiza1; Desmelati '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The objective of the research was to determine the effect the quality of freshwater mussel rendang with in varied weight, those were: weight 100 g (A1), 200 g (A2) and 300 g (A3). The method used was experiment and composed by using completely randomized design. The results showed that different weight of freshwater mussel meat affected to the quality of rendang produced. The highest quality of rendang was produced by the treatment of the using of 100 g mussel meat (A1) shown by the value of appearance 7.93%, scent 7.72%, sense 7.40% and texture 7.16%. The proximate composition consisted of moisture 54.03%, ash 3.14%, fat 14.85%, protein 23.23% and minerals that consisted of Ca 0.021 mg/g, K 0.019 mg/g, Na 0.035 mg/g, Fe 0.017 mg/g, heavy metals Cd 0.003 mg/g and Pb 0.008 mg/g.Keywords: Freshwater mussel, rendang, weight